A compact SNG-SRR Metamaterial sensor with enhanced sensitivity for biomedical applications - Md Shakhawat Hossen (23643853) (2025)
This paper presents a compact single-negative (SNG) split-ring resonator (SRR) metamaterial sensor developed for non-invasive wound dressing moisture monitoring. The sensor is fabricated on a Rogers RT5880 substrate (ɛr = 2.2, tan δ =0.009), occupies only 25 × 20 mm2, and operates reliably within the 2.0–2.8 GHz band, exhibiting a sharp −28dB transmission notch at 2.43 GHz. By exploiting epsilon-negative (ENG, ɛ < 0) behavior, the design achieves strong electromagnetic field confinement and a high surface current density of 98.8 A/m, enabling superior sensitivity and resonance selectivity compared to conventional SRR/CSRR sensors. The sensor’s performance was validated through both simulations and experiments using five wound dressing materials: (i) cotton gauze, (ii) hydrocolloid, (iii) polyurethane, (iv) alginate, and (v) hydrogel, under dry and soaked conditions. As the effective permittivity increased from ɛr = 2. 2 (dry) to ɛr = 18. 0 (20% blood concentration), the resonance frequency shifted from 2.43 GHz to 1.70 GHz, corresponding to a total shift of 0.73 GHz. This yielded normalized sensitivities ranging from 10.3% at 5% blood concentration to 30.0% at 20% blood concentration, with slope-based sensitivity peaking at 4.1% / ɛ near 10% blood concentration. Importantly, the sensor maintained a Q-factor above 30 across all loading conditions, confirming its robustness and measurement reliability. Operating within the 2.0–2.8 GHz range, the proposed sensor offers high sensitivity, stability, and ease of integration. This breakthrough SRR design demonstrates strong potential for enhancing wound management by enabling efficient, real-time, and precise moisture monitoring. Other Information Published in: Journal of Science: Advanced Materials and Devices License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jsamd.2025.101044